APLIKASI PENENTUAN RUTE TERPENDEK UNTUK BAGIAN PEMASA-RAN PRODUK ROTI SURYA DENGAN METODE BEST FIRST SEARCH - Aldisen Juniansyah; Masterjon Masterjon (Jurnal Media Infotama, 2016)
Policy decide journey route trajectory sequence part of this is marketing very is needed, because closely related with expense use of required oil fuel each time do marketing to marketing dot. Referred as closely related with expense of use of oil fuel perhaps progressively far marketing trajectory to be passed by to the same purpose, hence will be ever greater also expense which must by company. Pursuant to result of test-drive which have been conducted, application Determination short band route to part of surya bread product marketing with Best search first method, owning interesting appearance and way of using simple, easy to understanding.Keyword: Application, Shortest Route, Best First Search